The feminine protection of iliadic discourse: three interventions for the life of Hector - Moraes, Alexandre Santos de; Lessa, Fábio de Souza (Romanitas - Revista de Estudos Grecolatinos, 2013)
This article intends to reflect on a particular aspect of the notion of protection typically bound to the woman’s social action. Based on three successively passages in which three feminine characters seek to protect Hector’s life, we discuss the kind of protection that the Homeric poetry tends to associate to the woman’s world.